Linear Array Synthesis for Wireless Power Transmission Based on Brain Storm Optimization Algorithm - Guang Xu Liu; Qin Qin; Qing He Zhang (International Journal of Antennas and Propagation)
Based on the brain storm optimization algorithm, this paper proposed a new method to optimize the beam collection efficiency of the linear antenna array. In the process of optimization, constraints such as aperture size and minimum antenna spacing are considered. In this paper, the optimization with different antenna apertures, different antenna angles, and different array numbers are studied. A series of representative data and simulation results are given and the superiority of the brainstorming algorithm is demonstrated by comparing with the genetic algorithm.